Serum angiopoietin-like 3 levels are elevated in obese non diabetic men but are unaffected during an oral glucose tolerance test - Garcés, Maria Fernanda (2020)
This study aimed to determine ANGPTL3 serum levels in healthy young lean and obese non-diabetic men during an oral glucose tolerance test (OGTT) and correlate them with anthropometric, biochemical and hormonal parameters. A case–control study was carried out and 30 young obese non-diabetic (23.90 ± 3.84 years and BMI 37.92 ± 4.85 kg/m2) and 28 age-matched healthy lean (24.56 ± 3.50 years and BMI of 22.10 ± 1.72 kg/m2) men were included in this study. The primary outcome measures were serum basal ANGPTL3 and ANGPTL3–area under the curve (AUC) levels. The percentage of body fat was measured by dual-energy X-ray absorptiometry and biochemical, hormonal and insulin resistance indices were determined. Basal ANGPTL3 and ANGPTL3–AUC levels were significantly elevated (p < 0.05) in young obese subjects compared with lean subjects and were positively and significantly associated with different anthropometric measurements. Fasting ANGPTL3 serum levels were positively correlated with fasting insulin, leptin, Leptin/Adiponectin index and triglyceride—glucose index. Moreover, ANGPTL3–AUC was negatively correlated with Matsuda index. In this regard, chronically high ANGPTL3 levels in young obese subjects might favor triglyceride-rich lipoprotein clearance to replenish triglyceride stores by white adipose tissue rather than oxidative tissues.